القياس والافصاح المحاسبي للتكاليف البيئية وفق النظام المحاسبي المالي - بريزة, جلالي; سمية, دقاشي; صفاء, وصيف فائزة; وردة, قني (University of eloued جامعة الوادي, 2020)
"الملخــص يهدف هذا البحث إلى معرفة مدى مساهمة القياس واالفصاح المحاسبي عن التكاليف البيئية في تحسين الاداء البيئي للمؤسسات الاقتصادية, ومدى وعي الموظفين لأهميتهما في تحسين الأداء البيئي للمؤسسة وفق النظام المحاسبي المالي . اشتملت الدراسة على جانب نظري وأخر تطبيقي, واعتمدنا في هذه الدراسة على المنهج الوصفي, ولأختبار صحة الفرضيات قمنا بتصميم استمارة استبيان اشتملت على اسئلة واضحة وملائمة لعبارات المحاور المصاغة من جملة الفرضيات, وذلك بتطبيق سلم الثنائي نعم , لا للمحور الأول و الباقي وفق سلم ليكارث الخماسي موافق بشدة,......., غير موافق بشدة , و بعد التأكد من صحة و سالمة الاستبيان تم توزيعه على عينة الدراسة المتمثلة في مجموع المؤسسات الأقتصادية الجزائرية, و تم تطبيقها على جملة المؤسسات الاقتصادية المتواجدة في ولاية الوادي, ولاستخراج وتحليل النتائج استخدمنا جملة من القوانين الاحصائية في برنامج spss22. و بناء على هذا تم التوصل إلى جملة من النتائج متمثلة في : هناك درجة منخفضة من الوعي بأهمية القياس و الافصاح المحاسبي للتكاليف البيئية في المؤسسات محل الدراسة . كما هناك درجة منخفضة من الوعي بأهمية متابعة الأداء البيئي في المؤسسات الأقتصادية محل الدراسة. كما توصلنا إلى أنه هناك تأثير للقياس والافصاح البيئي في تحسين الاداء البيئي في المؤسسات محل الدراسة . كما أنه لا توجد فروق ذات دلالة معنوية إحصائية لمختلف محاور الاستبيان.""Abstract This research aims to find out the extent of the contribution of measurement and accounting disclosure of environmental costs to improving the environmental performance of economic institutions, and the extent of employee awareness of their importance in improving the environmental performance of the institution according to the financial accounting system.The study included a theoretical and an applied aspect, and we relied in this study on the descriptive approach ,In order to test the validity of the hypotheses ,we designed a questionnaire that included clear and appropriate questions for the expressions of the axes formulated from among the hypotheses, by applying the twoladder (yes, no) to the first axis and the rest according to the Lecarth five-scale scale (strongly agree, ......., disagree. Strongly), and after making sure of the validity and integrity of the questionnaire, it was distributed to the study sample represented by all Algerian economic institutions, and it was applied to all economic institutions located in the wilaya of the valley, and to extract and analyze the results we used a set of statistical laws in the SPSS program. And based on this, a number of results were reached, represented in:  There is a low level of awareness of the importance of accounting measurement and disclosure of environmental costs in the institutions under study.  There is also a low level of awareness of the importance of monitoring environmental performance in the economic institutions under study.  We also found that there is an impact of environmental measurement and disclosure on improving the environmental performance of the institutions under study.  Also, there are no statistically significant differences for the various axes of the questionnaire. "
مذكرة ماستر محاسبة
Keywords: التكاليف البيئية, القياس المحاسبي لتكاليف البيئية, اإلفصاح المحاسبي لتكاليف البيئية, األداء البيئي.; environmental costs, environmental costs accounting, environmental cost accounting disclosure, environmental performance.